Plasmacytoid Urothelial Carcinoma of the Bladder That Manifests Disseminated Carcinomatosis of the Bone Marrow: A Case Report of Extremely Rapid Progression - Nobuhiko Shimizu; Yoshinobu Moritoki; Nao Katsumi; Takahiro Yanase; Teruaki Sugino; Kazuhiro Kanemoto; Hidetoshi Akita; Takahiro Yasui (Case Reports in Urology)
Plasmacytoid urothelial carcinoma (PUC) of the bladder is a rare variant of invasive urothelial carcinoma (UC) with aggressive behavior. Despite its prognosis being poorer than that of conventional UC, a median overall survival of approximately 2 years is ensured when it is treated with radical cystectomy (RC), and few patients die within a few months of RC. In this paper, we report the case of a patient with PUC who developed widespread bone metastasis only 6 weeks after RC, which resulted in death within 2 months postoperatively.